The Role of Pancasila Education in Promoting Democratic Citizenship and Social Cohesion in Indonesia - Andhika Lungguh Perceka; Tomi Apra Santosa; Tardi Kurniawan; Ilwandri (Yayasan Darussalam Bengkulu, 2025)
This study aims to analyze the role of Pancasila Education in fostering democratic citizenship and strengthening social cohesion in Indonesia. The background to this research stems from increasing socio-political challenges, such as polarization, intolerance, low civic participation, and weakening national solidarity in a pluralistic society. This study uses a qualitative approach with a library study method, through a critical review of academic literature, educational policies, and key concepts regarding democracy, citizenship, and Pancasila values. The results of the study indicate that Pancasila Education has a strategic function in instilling the values of divinity, humanity, unity, deliberation, and social justice as an ethical foundation for democratic life. Pancasila Education plays a role not only in the transfer of ideological knowledge, but also in the formation of critical, tolerant, participatory, and responsible attitudes as citizens. In addition, the internalization of Pancasila values can strengthen social cohesion through respect for diversity, deliberative conflict resolution, and the strengthening of an inclusive national identity. However, the effectiveness of Pancasila Education depends heavily on a contextual, dialogical, and participatory learning approach, not simply normative memorization. This study concludes that Pancasila Education is a crucial instrument in building substantive democracy and maintaining social integration in Indonesia. Therefore, strengthening the curriculum, educator competencies, and experiential civic learning practices are urgently needed in the development of Pancasila Education.